Development of E-Static Learning Media Based on Smart Apps Creator (SAC) on Static Electricity Topic - Hadju, Asri Febriyani; Ntobuo, Nova Elysia; Paramata, Dewi Diana; Abdjul, Tirtawaty; Hermanto, I Made; Payu, Citron S. (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2025)
A virtual laboratory is an interactive science media assisted by computer applications in the form of science experiments. This research aims to determine the effect of using virtual laboratories on dynamic electricity topic on student learning outcomes. This type of research is quasi-experimental design research with a pretest-posttest control group design. The population in this study were all Class IX students of SMP Negeri 1 Wonosari in the current odd semester. The research results show that there is an influence on student learning outcomes. This is based on the hypothesis testing criteria, where t-count 2.09 is greater than t-table 2.02, and it can be concluded that hypothesis testing is t-count greater than t-table. The N-Gain test produced in the experimental class showed an N-Gain value of 1.18, which was included in the high criteria, while in the control class, the N-Gain value was 0.42, which was included in the medium criteria. The N-Gain value in the experimental class is included in the high criteria because the learning process uses a virtual laboratory in the experimental class. Virtual laboratories on dynamic electricity topic have an effect on student learning outcomes.